Underscoring long-term host-microbiome interactions in a physiologically relevant gingival tissue model - M. Adelfio; G. E. Callen; A. R. Diaz; B. J. Paster; X. He; H. Hasturk; C. E. Ghezzi (npj Biofilms and Microbiomes)
Abstract The human body houses many distinct and interconnecting microbial populations with long-lasting systemic effects, where the oral cavity serves as a pathogens’ reservoir. The correlation of different disease states strongly supports the need to understand the interplay between the oral tissue niche and microbiome. Despite efforts, the recapitulation of gingival architecture and physiological characteristics of the periodontal niche has yet to be accomplished by traditional cultural strategies. Here, we are showing for the first time the investigation of host–microbiome interactions in healthy conditions within a human oral tissue model over seven days. Our results indicated long-term host and microbiome viability, host barrier integrity, phenotypic functional response, and preservation of healthy microbial populations and interbacterial dialogs. This in vitro platform can maintain tissue homeostasis at the interface of the periodontal niche, thus, offering opportunities to identify predictive disease biomarkers and to develop intervention strategies to promote oral and overall health.